El agua en la Comunidad de Madrid - Alcolea Moratilla, Miguel Ángel; García Alvarado, José María (Observatorio Medioambiental, 2006)
The hydrographical characterization of the Community of Madrid it’s defined by the organization of it’s relief. Madrid’s rivers are supplied mainly by the important rainfall and snowfall in the mountains, which supplies to those rivers most of their flow. General hydrological disposition is N-S, influenced by the main water collector, Río Tajo. The whole hydrological elements which exists in the region have, most of them, an anthropic origin, that means men had changed the river flow in order to satisfy his necessities, mainly for the water supply in Madrid city. Water control and quality, very important in Madrid’s development are managed by Canal de Isabel II, state-owned company which grants the supplying an the quality of the water in most of Madrid’s Towns